Problematika Putusan Mahkamah Konstitusi dalam Mengonstruksi Batas Kewenangan Negara dan Otoritas Kelembagaan Publik - Tikka Dessy Harsanti; Rika Novitasari; Etty Umamy (Indonesian Social Science Review, 2026)
This study examines the role of decisions of the Constitutional Court of Indonesia in shaping and clarifying the boundaries of state authority and institutional power within Indonesia’s constitutional system. The research aims to analyze how Constitutional Court decisions contribute to the structuring of institutional powers and their implications for the principle of checks and balances. A socio-legal qualitative approach is employed through the analysis of 42 Constitutional Court decisions from 2019 to 2024, complemented by in-depth interviews with legal scholars, retired constitutional judges, and legal practitioners. The findings identify three main patterns of authority construction: annulment of norms, constitutional interpretation, and conditional decisions, with a notable prevalence of conditional rulings. The study indicates that, in certain cases, the Court does not merely review norms but also provides interpretative guidance for their application, particularly in situations involving legal ambiguity or potential normative gaps. While such practices may enhance constitutional effectiveness, they also highlight the need for clearer interpretative boundaries to avoid divergent understandings in inter-institutional relations. This study concludes that Constitutional Court decisions function as part of a dynamic process in the ongoing development of constitutional meaning within Indonesia’s evolving constitutional practice. Penelitian ini mengkaji peran putusan Mahkamah Konstitusi Republik Indonesia dalam membentuk dan menegaskan batas kewenangan negara serta otoritas kelembagaan publik dalam sistem ketatanegaraan Indonesia. Tujuan penelitian adalah menganalisis bagaimana putusan Mahkamah Konstitusi berkontribusi terhadap penataan kewenangan lembaga negara serta implikasinya terhadap prinsip checks and balances. Penelitian menggunakan pendekatan kualitatif sosio-legal melalui analisis terhadap 42 putusan Mahkamah Konstitusi periode 2019–2024, yang dilengkapi dengan wawancara mendalam bersama akademisi, hakim konstitusi purnatugas, dan praktisi hukum. Hasil penelitian menunjukkan tiga pola utama dalam konstruksi kewenangan, yaitu pembatalan norma, tafsir konstitusional, dan putusan bersyarat, dengan kecenderungan dominan pada putusan bersyarat. Temuan ini mengindikasikan bahwa dalam sejumlah perkara, Mahkamah tidak hanya melakukan pengujian norma, tetapi juga memberikan penafsiran yang memuat arahan penerapan norma dalam situasi ketidakjelasan atau potensi kekosongan hukum. Praktik tersebut di satu sisi berkontribusi terhadap efektivitas konstitusi, namun di sisi lain memunculkan kebutuhan akan kejelasan batas interpretasi agar tidak menimbulkan variasi pemaknaan dalam relasi antarlembaga negara. Penelitian ini menyimpulkan bahwa putusan Mahkamah Konstitusi berperan sebagai bagian dari proses dinamis dalam pembentukan makna konstitusional yang berkembang sesuai dengan konteks praktik ketatanegaraan.